MANAJEMEN WAKTU BELAJAR SISWA DITINJAU DARI JENIS KELAMIN DAN TINGKATAN KELAS - Mandasari, Fitri; Ardi, Zadrian; Nurfarhanah, Nurfarhanah; Nuzila Zahri, Triave (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research is motivated by the phenomenon in which some high school students are still unable to manage their time effectively in their daily lives, which impacts their academic performance. The purpose of this study is to describe and compare students' time management in learning based on gender and grade level. This study employed a descriptive comparative quantitative method. The population consisted of 591 tenth and eleventh grade students at SMA Pertiwi 1 Padang in the 2024–2025 academic year, with a sample of 274 students selected using proportional random sampling. Data collection was conducted using a self-control instrument with a Likert scale model. The data were analyzed using descriptive statistics and two-way ANOVA with the assistance of SPSS version 27. The results of the study revealed that: (1) the average score of students’ time management in learning, based on gender and grade level, was in the good category, and (2) there were no significant differences or interactions between gender and grade level in explaining students’ time management. The implications of these findings for Guidance and Counseling include the provision of informational services, group counseling services, and group guidance services.